The Psychometric Properties of the Norwegian version of Strengths and Difficulties Questionnaire, Parent Report (SDQ-P) - Kornør, Hege; Heyerdahl, Sonja (PsykTestBarn, 2017)
Description: Strengths and Difficulties Questionnaire (SDQ) is a set of parent-, teacher- and youth-reported questionnaires originally published in English by Robert Goodman in 1997. The Norwegian versions were published in 1999, based on a translation and back-translation by Einar Heiervang and colleagues. Robert Goodman holds the copyright. The parent version (SDQ-P) contains 25 items organised in five subscales. It is a parent report form to assess mental health, peer relations and prosocial behaviour in children aged 4-17 years. Completion takes a few minutes. Clinicians and teachers can administer and interpret SDQ-P scores. Literature search: Our systematic searches for psychometric evidence for the Norwegian SDQ-P version identified 408 unique references, of which 66 publications from 34 studies were included. Thirtyfive publications were reports from large population-based studies in Akershus, Bergen, Trondheim, Bodø, Østfold, Romsdal, Oslo and other parts of the country. Psychometrics: The large population-based studies contributed with regional norm data for children and adolescents aged 4 to 19. Researchers assessed the SDQ-P factor structure in three studies, and four studies and two substudies reported diagnostic accuracy data. Group comparisons between selected samples and reference groups also addressed the instrument’s validity, especially data for various diagnostic groups. Three studies examined the agreement between SDQ-P scores and scores from other, corresponding instruments. We identified measures of internal consistency (Cronbach’s alpha) in 21 of the included publications. Conclusions: The SDQ-P has regional norms, but there is a lack of national data. Expected group differences and confirmatory factor analyses support the construct validity of the instrument. Three scales have inadequate internal consistencies. The ability to detect children with a psychiatric diagnosis seems to be quite good. Still, the diagnostic accuracy is not sufficiently good to recommend the SDQ-P as a universal screening instrument. The Norwegian version of the SDQ-P may be appropriate for screening for psychiatric diagnoses in selected populations with high risk of mental health problems.